Inhibitors of the Autotaxin-Lysophosphatidic Acid Axis and Their Potential in the Treatment of Interstitial Lung Disease: Current Perspectives - Zulfikar S; Mulholland S; Adamali H; Barratt SL (Dove Medical Press, 2020)
Sabrina Zulfikar, Sarah Mulholland, Huzaifa Adamali, Shaney L Barratt Bristol Interstitial Lung Disease Service, North Bristol NHS Trust, Bristol, UKCorrespondence: Shaney L BarrattConsultant Respiratory Physician and Honorary Associate Researcher, North Bristol NHS Trust, Southmead Hospital, Southmead, Bristol BS10 5NB, UKEmail Shaney.Barratt@nbt.nhs.ukAbstract: Idiopathic pulmonary fibrosis is a progressive fibrosing interstitial lung disease for which there is no known cure. Currently available therapeutic options have been shown at best to slow the progression of the disease and thus there remains an urgent unmet need to identify new therapies. In this article, we will discuss the mechanisms of action, pre-clinical and clinical trial data surrounding inhibitors of the autotaxin-lysophosphatidic acid axis, which show promise as emerging novel therapies for fibrotic lung disease.Keywords: autotaxin inhibitors, autotaxin-lysophosphatidic acid axis, idiopathic pulmonary fibrosis, interstitial lung disease, fibrotic lung disease